The Future of Sovereignty in the Digital Age and Cybersecurity in Philosophical Dimension - Yunus, Nur Rohim (ADALAH, 2024)
The development of information and communication technology has created new complex challenges to state sovereignty. Cyber threats, digital attacks, and privacy violations are now serious problems that not only undermine state stability but also disrupt sovereignty in the digital space.